Load and Emission Characteristics of Pongamia Pinnata Oil in ACI Engine - Sankar, V.V. Arun; Arun Pravin, AP; Suresh, P (International Journal of Engineering and Technology, 2018)
As the world is running on fossil fuels there has been an ever increase in the depletion rate of these fuels. A promising and a best alternate to the fossil fuel is vegetable oils. Pongamia Pinnata oil is non edible in nature and is available abundantly in India. An experimental investigation is made to evaluate the performance, emission and combustion characteristics on a compression ignition engine by using methyl ester of pongamia with mineral diesel in different proportions. Pongamia methyl ester was blended with diesel in proportions of 50% and 100% by mass and the results are tabulated and evaluated under various test conditions. The performance parameters were found to be very close to that of mineral diesel. The brake thermal efficiency and mechanical efficiency were better than mineral diesel for some specific blending ratios under certain loads. The Efficiency and emission characteristics were also studied and levels of carbon dioxide, carbon monoxide, nitric oxide and hydrocarbons were found to be equal than pure diesel.